Stylistic analysis of deictic expressions in President Benigno Aquino III’s October 30th speech - Quinto, Edward Jay Mansarate (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
This paper analyses how the President of the Philippines, Benigno Simeon Aquino III, or simply PNoy, deployed persons, time, location and social relationships in the English translation of his October 30th televised national address and what meaning and effect does such deployment of referring expressions bring about in understanding the nature of the political speech. Using the frameworks of Hanks (2005) and Buhler (1934), this paper examines how, PNoy strategically sets up the deictic field by placing several personal, temporal, spatial and social deictic expressions in what initially is a ground zero. The deployment creates a deictic field in which the Filipino people are situated at deictic centre and the President and his critics are in binary opposition. PNoy’s deployment of deictic expressions is very effectively done so that the deictic centre is persuaded to judge the president and his government favourably and the binary opposite in the deictic field, unfavourably. Through a systematic stylistic account of deixis in political speech, this paper argues that not only personal deixis, as previous studies put forth, but also temporal, spatial and social deixis helps political actors to persuade the audience in their favour and ultimately boost leverage in their political discourse and outside.